Evaluation of the recovery of thermal aging embrittlement of CF8M cast stainless steels after reversion heat treatments. (July 2015) - Jang, Changheui; Jang, Hun; Hong, Sunghoon; Lee, Jae Gon
Abstract: The degradation of mechanical properties caused by the thermal aging embrittlement of cast stainless steels (CASSs) is considered one of the key issues that should be resolved for the continued operation of nuclear power plants. In this study, the effects of reversion heat treatments on the mechanical properties of CF8M were evaluated by tensile and small punch tests. The reversion heat treatments were performed at 550 °C and 600 °C for two heats of CF8M containing 11% and 32% of ferrites. After the reversion heat treatments (R-HT), the ductility and small punch energy of the aged CF8Ms were effectively recovered. The re-aging embrittlement behaviors of the recovered CF8M were less severe than the initial aging behaviors. Furthermore, the application of the R-HT to the as-received CF8M also reduced the degree of thermal aging embrittlement. The fracture surface analyses also confirmed the observed changes in mechanical properties. Finally, the optimum reversion heat treatment condition for the recovery of thermal aging embrittlement of CF8M was proposed.